Dual-functional eco-friendly liquid metal/boron nitride/silk fibroin composite film with outstanding thermal conductivity and electromagnetic shielding efficiency. (April 2023) - Lv, Zhe; Kong, Lijing; Sun, Puqing; Lin, Yongxing; Wang, Yanyan; Xiao, Chao; Liu, Xianglan; Zhang, Xian; Zheng, Kang; Tian, Xingyou
Abstract: A composite film with gradient structure constructed through infiltrating liquid metal (LM)/Polyvinyl alcohol (PVA) solution into a boron nitride nanosheet/silk fibroin (BNNS/SF) electrospinning film was developed. The gravity driven settling and PVA welding give rise to the gradient distribution of LM, and the LM/BNNS/SF composite film was obtained following the mold pressing. Benefitting from the LM, the LM/BNNS/SF composite film exhibits a highest through-plane thermal conductivity (TC) about 3.24 W/m·K and a highest in-plane TC about 12.53 W/m·K, together with outstanding electromagnetic shielding efficiency, reaching to 75 dB in X band. Moreover, the LM/BNNS/SF composite film also exhibits good surface insulativity, exhibiting great potential in electronic packaging material field. Graphical abstract: Image 1 Highlights: A layered gradient penetrative structure has been constructed by electrospinning, coating process and cold pressing. The through-plane thermal conductivity has been controlled by the adjustment of structure. The EMI shielding performance has been controlled by the adjustment of structure.